Optimalisasi Rasio Permodalan melalui Kinerja Keuangan, Ukuran Bank, dan Produk Bagi Hasil Bank Umum Syariah - Sistiyarini, Evi; Nasution, Zubaidah; Wulandari, Dewi Ayu (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
Banks require adequate capital to foresee risks in their operating activities. Finding the factors influencing Islamic commercial banks' capital adequacy ratio (CAR) is the aim of this study. The higher the capital owned by the bank, the stronger the bank is in facing risks. One indicator of banking capital can be seen in the Capital Adequacy Ratio (CAR). The dependent variable is capital adequacy as measured by CAR. The independent variables used are FDR, ROE, NPF, BOPO, bank size, and profit-sharing products. This study uses panel data regression analysis to process data collected from bank financial statements. The results of the study indicate that the FDR variable has a positive but insignificant effect on CAR. ROE, NPF, BOPO, and profit-sharing products have a significant negative effect on CAR in Islamic commercial banks. Bank size has a significant positive effect on CAR in Islamic commercial banks. This finding suggests that the bank's size, profit-sharing plans, and financial performance all play a significant role in determining its capital.